Efficacy of Metabolic Therapy in the Complex Treatment of Necrotizing Enterocolitis in Newborns - L. G. Bochkova; A. S. Eiberman; Y. V. Chernenkov (Детские инфекции (Москва))
Treatment of necrotizing enterocolitis (NEC) in newborns remains an urgent problem due to the risk of severe complications and high mortality in these patients. The search for new therapeutic technologies to reduce the number of adverse outcomes and improve the quality of life of children is one of the modern tasks of neonatology. The aim of the study was to study the clinical results of the use of Cytoflavin® (succinic acid, inosine, nicotinamide, riboflavin) as part of complex therapy in the conservative treatment of NEC in newborns. Materials. A total of 151 premature newborns with stage I—II NEC were monitored. The study group consisted of 78 infants with NEC whose treatment included cytoflavin. The comparison group consisted of 73 infants with NEC who were treated according to the traditional regimen. Results. When analyzing the course of the early neonatal period, it was revealed that the duration of mechanical ventilation in the children of the main group was significantly shorter (36.3 ± 4.9 days) compared to the second group (58.7 ± 4.8 days). Restoration of intestinal passage in children treated with cytoflavin occurred in 62.4 ± 11.0 hours, which is significantly faster than in the comparison group (98.2 ± 10.4 hours). The number of children in the study group transferred to the surgical department (6.41%) was significantly lower compared to the number of severe complications in the second group (15.06%). Conclusion. A positive result of the effect of metabolic therapy with the use of cytoflavin on the course of NEC in newborns is a significant shortening of the duration of their treatment with subsequent transfer to a physiological method of nutrition and a decrease in the incidence of severe surgical complications.